Predicting long-term compressive creep of concrete using inverse analysis method. (15th October 2016) - Ghasemzadeh, Farnam; Manafpour, Amir; Sajedi, Siavash; Shekarchi, Mohammad; Hatami, Mona
Highlights: Prediction of creep was improved using proposed inverse analysis methodology. Sample results from different studies were used to verify proposed methodology. Various statistical indicators were used to evaluate the accuracy of proposed method. Proposed method had lower prediction errors compared to available creep models. For certain creep models, the proposed method was too sensitive and thus not appropriate. Abstract: Long-term creep prediction has been a major issue of concern in designing concrete structures for some time. Many researchers have developed various models in order to predict uni-axial compressive concrete creep, however a more precise and reliable method of prediction is still required. This investigation introduces an inverse analysis (IA) method that utilizes short-term creep measurements under certain conditions to predict long-term results under the same conditions. The proposed IA method was applied to seven different prediction models and the experimental results of six specimens (from three different studies) were chosen to verify the reliability of this method. It was concluded that the IA method is able to successfully improve the accuracy of prediction and has a comprehensive range of application.